Integrated model for pricing, delivery time setting, and scheduling in make-to-order environments - Hamid Sattari Garmdare; M. M. Lotfi; Mahboobeh Honarvar (Journal of Industrial Engineering International, 2018)
Usually, in make-to-order environments which work only in response to the customer's orders, manufacturers for maximizing the profits should offer the best price and delivery time for an order considering the existing capacity and the customer's sensitivity to both the factors. In this paper, an integrated approach for pricing, delivery time setting and scheduling of new arrival orders are proposed based on the existing capacity and accepted orders in system. In the problem, the acquired market demands dependent on the price and delivery time of both the manufacturer and its competitors. A mixed-integer non-linear programming model is presented for the problem. After converting to a pure non-linear model, it is validated through a case study. The efficiency of proposed model is confirmed by comparing it to both the literature and the current practice. Finally, sensitivity analysis for the key parameters is carried out.
Keywords: 650; Make-to-order; Pricing; Delivery time; Order scheduling; Mixed-integer non-linear program